Factors that Caused Decline Crime Rates in Developed Western Countries (1990-2008) - Kizmaz, Zahir (Istanbul Univ, 2021)
Recently, one of the most significant changes in developed countries has been the decrease in crime rates. The era following the 1960s particularly witnessed an increase in crime rates in developed western countries, and these rates attained their peaks in several countries around the early and mid-1990s. However, following this period, incidents of crime began declining gradually. Furthermore, USA experienced a 43% decline in homicide rates between 1991-2001. During this period, the overall incidents of violent and property crimes decreased by 34% and 29%, respectively. In a study conducted on murder trends in 53 developed and developing countries spanning the years 1990-2005, a decrease in homicide rates was noted in most of the countries that had been studied. Undoubtedly, this decline is not limited to violent crimes. This article focuses on the significant decline in crime rates in developed western countries-especially in the USA and European countries-since the 1990s and elucidates the socio-economic, demographic, cultural, and legal causes of such a decline. The current study seeks to determine which of these factors are the primary causes of a decline in crime rates and the extent to which the factors considered effective in lowering the crime rates in the United States and other western countries are similar or different.
Keywords: Crime decline; crime trends; the USA and crime; European countries and crime